Design of volatile organic compounds profiles of roasted Coffea arabica extracts produced by supercritical and conventional solvents - de Toledo, Paulo R. A. B. [UNESP]; de Melo, Marcelo M. R.; Rodrigues, Vítor H.; Pezza, Helena R. [UNESP]; Rocha, Sílvia M.; Toci, Aline T.; Pezza, Leonardo [UNESP]; Portugal, Inês; Silva, Carlos M. (Oxford University Press (OUP), 2022)
This work addresses the potential of supercritical fluid extraction (SFE) to design volatile organic compounds (VOCs) profiles using roasted Coffea arabica. On the whole, 57 VOCs were identified by HS-SPME/GC–MS. A full factorial design was adopted to study the effect of pressure (180 and 300 bar), temperature (40 and 80 °C) and ethanol content (0 and 5 wt.%). The total extraction yield ranged from 1.4 wt.% to 9.8 wt.%. At 180 bar and 80 °C, two extracts exhibited VOCs amount up to 3.5 times higher than the dichloromethane extract. Temperature and pressure favoured VOCs amount and total yield in conflicting ways, and ethanol had a negligible effect on VOCs amount. At 180 bar and 80 °C, the VOCs profile revealed a reinforcement of pyrroles, phenols, cyclopentenes and pyrans, at the expense of pyridines, carboxylic acids and furans. Hence, this essay evidences the potential of SFE to engineer coffee VOCs profiles.
Keywords: Design of experiments; HS-SPME/GC–MS; roasted coffee; supercritical fluid extraction; VOCs profile